Local Government Policy Concerning the Development of Athletes of the Pencak Silat Martial Sports Branch in Lahat Regency - Senoadji Nugroho; M. Taheri Akhbar; Mutiara Fajar (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to describe how the local government's policy regarding the development of athletes in the pencak silat martial arts branch in Lahat district, the research was carried out in Lahat district. The method used in this study is a qualitative descriptive method, the subjects of this study were informants from Dispora, IPSI, and Heads of Universities. Data collection techniques using triangulation techniques in the form of observations, interviews and documentation. data analysis techniques performed after data collection. From the results of data analysis, it can be explained that the local government has carried out and is in the process of developing sports, especially in the field of coaching both from human resources and facilities and infrastructure.